Lutein-Rich Beverage Alleviates Visual Fatigue in the Hyperglycemia Model of Sprague–Dawley Rats - Qiong Tang; Sishan Wei; Xiangyi He; Xiaodong Zheng; Fei Tao; Pengcheng Tu; Bei Gao (Metabolites, 2023)
Asthenopia is a syndrome based on the symptoms of eye discomfort that has become a chronic disease that interferes with and harms people’s physical and mental health. Lutein is an internationally recognized “eye nutrient”, and studies have shown that it can protect the retina and relieve visual fatigue. In this study, lutein was extracted from marigold (Tagetes erecta L.) and saponified. The purified lutein concentration measured by HPLC was 50.12 mg/100 g. Then, purified lutein was modified to be water-soluble by nanoscale modification and microencapsulation technology. Water-soluble lutein was then mixed with a leaching solution of Chinese wolfberry and chrysanthemum to make a functional beverage. The effects of this beverage on hepatic antioxidant enzymes and the alleviation of visual fatigue in a rat model of diabetes were investigated for 4 weeks. Lutein intake of 0.72 (medium-lutein beverage group) and 1.44 mg/mL (high-lutein beverage group) relieved visual fatigue, ameliorated turbidity symptoms of impaired crystalline lenses, reduced hepatic MDA concentration, increased hepatic GSH concentration, and significantly increased the activities of the hepatic antioxidant enzymes SOD, CAT, GSH-Px, and GR in rats. These data suggest that a lutein-rich beverage is an effective and harmless way to increase the total anti-oxidation capacity of lenses and alleviate visual fatigue.